Effect of Dapagliflozin on Atrial Fibrillation in Patients With Type 2 Diabetes Mellitus: Insights From the DECLARE-TIMI 58 Trial. Issue 15 (14th April 2020) - Zelniker, Thomas A.; Bonaca, Marc P.; Furtado, Remo H.M.; Mosenzon, Ofri; Kuder, Julia F.; Murphy, Sabina A.; Bhatt, Deepak L.; Leiter, Lawrence A.; McGuire, Darren K.; Wilding, John P.H.; Budaj, Andrzej; Kiss, Robert G.; et al.
Abstract : Background: Atrial fibrillation (AF) and atrial flutter (AFL) are associated with both diabetes mellitus and its related comorbidities, including hypertension, obesity, and heart failure (HF). SGLT2 (sodium-glucose cotransporter 2) inhibitors have been shown to lower blood pressure, reduce weight, have salutary effects on left ventricular remodeling, and reduce hospitalization for HF and cardiovascular death in patients with type 2 diabetes mellitus. We therefore investigated whether SGLT2 inhibitors could also reduce the risk of AF/AFL. Methods: DECLARE-TIMI 58 (Dapagliflozin Effect on Cardiovascular Events–Thrombolysis in Myocardial Infarction 58) studied the efficacy and safety of the SGLT2 inhibitor dapagliflozin versus placebo in 17 160 patients with type 2 diabetes mellitus and either multiple risk factors for atherosclerotic cardiovascular disease (n=10 186) or known atherosclerotic cardiovascular disease (n=6974). We explored the effect of dapagliflozin on the first and total number of AF/AFL events in patients with (n=1116) and without prevalent AF/AFL using Cox and negative binomial models, respectively. AF/AFL events were identified by search of the safety database using MedDRA preferred terms ("atrial fibrillation, " "atrial flutter"). Results: Dapagliflozin reduced the risk of AF/AFL events by 19% (264 versus 325 events; 7.8 versus 9.6 events per 1000 patient-years; hazard ratio [HR], 0.81 [95% CI, 0.68–0.95]; P =0.009). The reduction in AF/AFL events was consistent regardless of presence or absence of a history of AF/AFL at baseline (previous AF/AFL: HR, 0.79 [95% CI, 0.58–1.09]; no AF/AFL: HR, 0.81 [95% CI, 0.67–0.98]; P for interaction 0.89). Similarly, presence of atherosclerotic cardiovascular disease (HR, 0.83 [95% CI, 0.66–1.04]) versus multiple risk factors (HR, 0.78 [95% CI, 0.62–0.99]; P for interaction 0.72) or a history of HF (HF: HR, 0.78 [95% CI, 0.55–1.11]; No HF: HR, 0.81 [95% CI, 0.68–0.97]; P for interaction 0.88) did not modify the reduction in AF/AFL events observed with dapagliflozin. Moreover, there was no effect modification by sex, history of ischemic stroke, glycated hemoglobin A1c, body mass index, blood pressure, or estimated glomerular filtration rate (all P for interaction >0.20). Dapagliflozin also reduced the total number (first and recurrent) of AF/AFL events (337 versus 432; incidence rate ratio, 0.77 [95% CI, 0.64–0.92]; P =0.005). Conclusions: Dapagliflozin decreased the incidence of reported episodes of AF/AFL adverse events in high-risk patients with type 2 diabetes mellitus. This effect was consistent regardless of the patient's previous history of AF, atherosclerotic cardiovascular disease, or HF. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT01730534. Abstract : Supplemental Digital Content is available in the text.